Integrated project management - Barkley, Bruce T. (McGraw-Hill, 2006)
This is a road-map to effectively implementing business strategies that span the entire organization by using project management tools and techniques. Readers will learn how to overcome organizational and departmental barriers in order to achieve fully integrated, enterprise-wide project management success.